METAMORFOSES DO MELODRAMA NO PERIODISMO BRASILEIRO DA DÉCADA DE 1930 - Soares Borges, Camila; França, George Luiz (Inventário, 2025)
Born from the search for mechanisms to restore order in the context of the French Revolution and the rise of the bourgeoisie, melodrama extrapolates the condition of a textual gender and corresponds to a mode of cultural imagination linked to the construction of modern national identities. The genre survives and exceeds the French context and the nineteenth century, making itself present in Brazil since that period, being discussed in magazines and newspapers and becoming other cultural objects. This article evaluates the uses of the term "melodrama", the problems and the valuations associated with it between the years 1930 to 1939 in Brazilian newspapers and magazines made available by the Fundação Biblioteca Nacional at the Hemeroteca Digital. The researchers attempted to construct a corpus cataloging reviews, opinion articles, fragments of ads and news in Brazilian journals that contained the term "melodrama" and analyzed it with the theorizations of Martín-Barbero, Thomasseau and Brooks. As a result, it’s possible to understand the various valuations associated with the term melodrama, establish patterns present in the cataloged data, establish intersections between melodrama and racial and gender issues, besides seeing changes in the artistic scene that culminated in different receptions of the Brazilian press trying to understand the metamorphoses of melodrama. Moreover, it’s possible to verify how the moralizing ideals disseminated by this artworks impact society, how melodrama composes productions of the most varied aspects and how melodramatic imagination influenced the construction of our modern imaginary.